2012
DOI: 10.1152/ajpheart.00271.2012
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α impairs endothelial function in adipose tissue resistance arteries of mice with diet-induced obesity

Abstract: ; P Ͻ 0.05) and the homeostatic model assessment (HF, 64.1 Ϯ 4.3 vs. NC, 85.7 Ϯ 6.4; P ϭ 0.05). HF diet-induced metabolic dysfunction was concomitant with a proinflammatory eWAT phenotype characterized by greater macrophage infiltration (HF, 3.9 Ϯ 0.8 vs. NC, 0.8 Ϯ 0.4%; P ϭ 0.01) and TNF-␣ (HF, 22.6 Ϯ 4.3 vs. NC, 11.4 Ϯ 2.5 pg/dl; P Ͻ 0.05) and was associated with resistance artery dysfunction, evidenced by impaired endotheliumdependent dilation (EDD) (maximal dilation; HF, 49.2 Ϯ 10.7 vs. NC, 92.4 Ϯ 1.4%; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 45 publications
(64 reference statements)
1
50
0
Order By: Relevance
“…For example, adipose tissue plays an integral role in endothelial inflammation through the release of TNF-α and subsequent expression of inflammatory cytokines and adhesion molecules exacerbating obesity-related vascular disease (44). Consistent with our hypothesis, metformin exhibited the effects of the AMPK-PARP-1-Bcl-6 anti-inflammatory cascade in adipocytes to mitigate TNF-α-induced inflammation (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…For example, adipose tissue plays an integral role in endothelial inflammation through the release of TNF-α and subsequent expression of inflammatory cytokines and adhesion molecules exacerbating obesity-related vascular disease (44). Consistent with our hypothesis, metformin exhibited the effects of the AMPK-PARP-1-Bcl-6 anti-inflammatory cascade in adipocytes to mitigate TNF-α-induced inflammation (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…However, this might indicate that more TNF-␣ is bound to its receptor thereby exerting more biological activity and vascular dysfunction in obese preeclamptic women or that, in obesity, less TNF-␣ is needed to promote vascular dysfunction. In support of this theory, although only performed in male mice, it was demonstrated that HFD-induced obesity is associated with greater TNF-␣-induced impairment of endothelium/NOmediated vasorelaxation in resistance arteries isolated from white adipose tissue even though plasma levels of this cytokine were similar between normal diet and HFD groups (41). It should be considered that this phenomenon may result from local production of TNF-␣ in adipose or the vasculature per se that can impact arterial function without reaching the circulation.…”
Section: Effects Of Obesity On Placental Ischemia-induced Endothelialmentioning
confidence: 94%
“…Previous studies have demonstrated an impairment of relaxant responses in the aorta, mesenteric 9 , femoral, and coronary arteries 10 in experimental models of obesity, that were associated with diminished NO release. The impaired vascular function and an increased vascular oxidative stress observed in obesity were associated with increased levels of inflammatory adipocytokines such as leptin, and tumor necrosis factor alpha -TNF-α, as well as decreased levels of anti-inflammatory adipocytokines such as adiponectin 11 .…”
Section: Vascular Dysfunction In Obesitymentioning
confidence: 99%